(untitled) (Baltic Journal of Sport and Health Sciences, 2016)
Background. Relatively little knowledge is available to date about moral values among adolescents. As participation in sports activities may contribute to positive youth development, this study aims to examine the relations between adolescents’ involvement in sports activities and the internalisation of their moral values. We assessed this relationship with respect to gender as well. Methods. The sample included 385 adolescents (192 girls and 193 boys) between 13 to 16 years of age (M age = 14.6, SD =1.11); 43.4% (n = 167) of the research participants were involved in competitive sports. The studied adolescents had participated in their respective sport for an average of 2.97 (SD = 1.12) years. The internalisation of moral values was assessed using the 24-item adolescent-report Moral Values Internalisation Questionnaire (Hardy, Padilla-Walker, & Carlo, 2008). Four forms of value regulation were assessed (external, introjected, identified and integrated). Overall value internalisation was also evaluated. Results. Significant differences were found between adolescent involvement in sports activities and external regulation (p < .05), introjected regulation (p < .01), identified regulation (p < .05) as well as integrated regulation (p < .01). In depth analyses showed that the four forms of value regulations were higher for the athletes with experience up to three years and tended to be lower in the group of athletes with higher sports experience. The same relationship was established in the sample of boys, but not in that of girls. Conclusions. The research results demonstrated that the identified regulation manifested more than other regulations did (external, introjected and integrated). Adolescent athletes possessed higher points of moral value internalisation in all regulations than adolescent non-athletes. Nevertherless, referring to sports experience, the internalisation forms of moral values of adolescent athletes with more than the three-year sport experience did not differ in comparison with those of adolescent non-athletes. Research results show that the internalisation of moral values for adolescents with higher sports experience is lower compared to that of adolescents with lower sports experience. Keywords: adolescents’ moral values, participation in sport, sports experience.